The Role of Transformational Leadership in Enhancing Employee Performance: A Systematic Literature Review - Ahmad Hadi Saptaji; Ismail Nurdin (Global Writing Academica Researching & Publishing, 2026)
The success of bureaucratic reform in Indonesia depends heavily on the performance of civil servants (ASN) as the primary providers of public services, with leadership recognized as one of the key determinants of that performance. Transformational leadership is regarded as genuine leadership, as it directs organizations toward goals never previously achieved, in contrast to leadership styles that merely preserve the status quo. This study aims to examine the influence of transformational leadership on improving employee performance through a Systematic Literature Review (SLR) approach. Data were collected by searching for articles on Google Scholar using the keyword